Team Building - a Tool for Management - Sridharan, Sunaina; John, Romate; Bhogle, Sudha (Ushus Journal of Business Management, 2021)
This paper aims at analyzing the present definitions of a team and team building as a process. Existing models and research conducted on team and team building have been reviewed and evaluated. The tools used for evaluating team effectiveness and team building, approaches towards team roles and the changing views on team building over the years have also been discussed. The paper raises questions on the emphasis on interpersonal communication in teams in the present world scenario and the need to develop specific tools to meet role specific or organisation specific requirements with regard to team building. Finally, this paper also attempts to review the limitations in current research and training in team building and their applications, and suggests alternatives for further research.